PENERAPAN MODEL PEMBELAJARAN PENEMUAN TERBIMBING UNTUK MENINGKATKAN KEMAMPUAN MENULIS DIALOG SESUAI UNGGAH-UNGGUH BASA DAN SIKAP SANTUN - Leliana Anisa; Atikah Anindyarini; Rahmat Rahmat (Sabdasastra : Jurnal Pendidikan Bahasa Jawa, 2019)
This research was aimed to improve student’s ability in writing appropriate with unggah-ungguh basa and well-mannered attitude in class VII E of  SMP 5 Madiun, using guided discovery learning model. This class action research was conducted in two cycles, which every cycles consisted of action planning, action, observing, and reflecting. The subject of the research were the students of class VII E SMP Negeri 5 Madiun which consist of 34 students. The sources of the data were from the teacher, the students, and teaching-learning process. The technique of collecting data used were test, observation, interview, and documentation. Triangulation technique, which were triangulation data and triangulation method, was used  to test the validity of the data. The technique to analize the quantitative data was statistic descriptive comparative technique, whereas to analize qualitative data was critical analysis technique. The research model used spiral model (planning, acting, observing, and reflecting). The result of this research showed that after implemented guided discovery learning model, students’s ability in writing appropriate with unggah-ungguh basa and well-mannered attitude have changed to be better. Based on the test of students’s ability in writing appropriate with unggah-ungguh basa, the percentage of the class passing grade increased from 37,5% in pre-cycle, became 66,7% in cycle 1 and 79,2% in cycle 2 from the total of 24 students. Meanwhile the improvement of well-mannered attitude based on observation and questionnaire about well-mannered attitude, was 41,7% during pre-cycle, then improved to 70,8% in cycle 1 and 87,5% in cycle 2. Based on the result and the discussion of the research, the conclusion that can be drawn is that the implementation guided discovery learning model can improve students’s ability in writing appropriate with unggah-ungguh basa and well-mannered attitude in class VII E of SMP 5 Madiun.